Muhammad Zaini Djalaluddin: Model Ulama Kalimantan Barat - Abdillah, Zulkifli (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
This study examines the existance of scholars (ulama) in West Kalimantan that has a rather characteristic differences with scholars in Java. This study using oral history models through case studies tracing the biography of a prominent scholar (ulama), namely Ustaz Haji Muhammad Zaini Jalaluddin. By using the concept of charismatic authority and rational-legal authority of Max Weber, this study concludes three things. First, the source of authority charismatic scholars (in this case Ustaz Jalal) is genealogy, the process of education (mastery of Islamic kwowledge) and the quality of a strong personality. Second, charismatic authority into capital to get a legal - rational authority. Third, when the legal-rational authority is lost from a scholar (ulama) himself so he would be accepted as normal by the people over at his charismatic authority is maintained. Keywords: Ulama, CharismaticAuthority, Legal-Rational AuthorityÂ